Legal Justice in Returning Losses to Victims of Illegal Investment Criminal Acts - Santoso, Bambang; Arifin, Muhammad; Ramlan, Ramlan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Regarding Legal Justice in Restitution of Victims of Criminal Acts, further provisions regarding the procedure for carrying out conditional sentences (voorwaardelijke veroordeling) are regulated in Article 276 of the Criminal Procedure Code which states: "In the event that the court imposes a conditional sentence, its implementation shall be carried out with serious supervision and observation and in accordance with the provisions of the Law." According to Muladi, conditional sentences (voorwaardelijke veroordeling) are a form of humane criminal law, namely by prioritizing prevention, not only oriented towards actions but also towards people who commit crimes, which are tat-tatterstrafrecht, placing social welfare as the ultimate goal, oriented towards the future. The mechanism for applying compensation is also regulated in Article 275 of the Criminal Code which states: "If more than one person is convicted in one case, then the court costs and/or compensation as referred to in Article 274 shall be borne by them jointly in equal proportions". The explanation is explained as follows “Because the defendants in the case referred to in this article are jointly sentenced because they are accused of committing a crime in one case, it is reasonable if the court costs and/or compensation are borne jointly in equal proportions